2006
DOI: 10.1016/j.msea.2006.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength improvement of a 4140 steel by gas nitriding: Influence of notch severity

Abstract: Fatigue failure of a gas-nitrided 4140 steel under axial cyclic loading results from a competition between surface crack initiation in the nitrided case and internal "fish-eye" cracking inside the core material. When nitriding is deep enough, the internal mechanism prevails in smooth specimens and fatigue strength improvement as compared to base metal is about 20%. In the present study, three V-notched specimens (blunt -medium -severe) are designed to be representative of the stress gradient (i) in a small rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 9 publications
1
33
0
2
Order By: Relevance
“…Due to its good balance of strength, toughness and wear resistance, 42CrMo high-strength steel is widely used for many general purpose parts including automotive crankshaft, rams, spindles, etc. In the past, many investigations have been carried out on the behaviors of 42CrMo steel (Limodin and Verreman, 2006). Smoljan (2004) found that it is possible in effective way to improve a steel strength and toughness by the combined cyclic heat treatment consisted of temperature cycling followed by twice quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its good balance of strength, toughness and wear resistance, 42CrMo high-strength steel is widely used for many general purpose parts including automotive crankshaft, rams, spindles, etc. In the past, many investigations have been carried out on the behaviors of 42CrMo steel (Limodin and Verreman, 2006). Smoljan (2004) found that it is possible in effective way to improve a steel strength and toughness by the combined cyclic heat treatment consisted of temperature cycling followed by twice quenching.…”
Section: Introductionmentioning
confidence: 99%
“…O aumento do parâmetro de rede é proveniente da presença de nitrogênio intersticial e, após a saturação do elemento, pela formação de nitretos e que geram um aumento de tensão residual compressiva na camada nitretada. Esse aumento no nível de tensões residuais na superfície de um componente mecânico melhora a sua vida em fadiga [6] [14].…”
Section: Discussionunclassified
“…The interest of this treatment in the industrial applications justifies the number of studies which were devoted to this subject [1][2][3][4][5][6][7][8][9]. This reveals that the in-depth penetration crack resistance of hardening elements (N 2 ), of the hardness of these layers [4,5,6,8] as well as the distribution of the residual stresses [7,9,10].…”
Section: Introductionmentioning
confidence: 99%